Sharia Compliance and Islamic Corporate Governance in The Islamic Bank in Indonesia - Mellya Embun Baining; Novi Mubyarto; Nurjanah Nurjanah (Asosiasi Dosen Akuntansi Indonesia, 2021)
This study was conducted to examine the effect of Sharia Compliance and Islamic Corporate Governance on indications of fraud in Islamic Banks in Indonesia for the 2015 2019 period. Sharia Compliance with the proxies of Islamic Income Ratio, Profit Sharing Ratio, Islamic Investment Ratio, Zakat Performance Ratio and Islamic Corporate Governance are independent variables. And fraud on Islamic Banks is the dependent variable used in this study.The populations used in this study were all Islamic Commercial Banks (BUS) registered with the Financial Services Authority in the period 2015 to 2019. The sample in this study used the method. Purposive sampling. In this study there were 11 Islamic Banks with a research period of 5 years and the sample used in this study amounted to 41 after being transformed into semi logs and Generalized Least Square (GLS). In this study using multiple regression analysis method, panel data is processed using Eviews 10 and Microsoft Excel 2016. The results of this study show that the Islamic Income Ratio has no effect on Fraud, Profit Sharing Ratio has a negative effect on fraud, the. Islamic Investment Ratio has a positive effect Fraud, Zakat Performance Ratio not affect Fraud in Islamic Banks. variable is Islamic Corporate Governance not affect Fraud in Islamic Banks.